2015
DOI: 10.1021/acs.estlett.5b00008
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfone Membranes Modified with Bioinspired Polydopamine and Silver Nanoparticles Formed in Situ To Mitigate Biofouling

Abstract: The surface of a polysulfone membrane was modified with a bioinspired polydopamine (PDA) film followed by the in situ formation of silver nanoparticles (AgNPs) to mitigate membrane biofouling. The PDA modification enhanced the membrane's bacterial anti-adhesive properties by increasing the surface hydrophilicity, while AgNPs imparted strong antimicrobial properties to the membrane. The AgNPs could be generated on the membrane surface by simply exposing the membrane to AgNO 3 solutions. Ag + ions were reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 49 publications
6
65
1
Order By: Relevance
“…Silver is one of the most common potent 7 broad-spectrum biocides that has very low toxicity to human [10]. It has been utilized in 8 many studies and demonstrated to be effective in inhibiting bacteria growth on membrane 9 surface [11][12][13][14][15][16][17][18][19][20][21][22]. To better control the release rate of Ag, zero-valent Ag instead of Ag + ion is preferred, usually in the form of Ag nanoparticles (AgNP) [11].…”
mentioning
confidence: 99%
“…Silver is one of the most common potent 7 broad-spectrum biocides that has very low toxicity to human [10]. It has been utilized in 8 many studies and demonstrated to be effective in inhibiting bacteria growth on membrane 9 surface [11][12][13][14][15][16][17][18][19][20][21][22]. To better control the release rate of Ag, zero-valent Ag instead of Ag + ion is preferred, usually in the form of Ag nanoparticles (AgNP) [11].…”
mentioning
confidence: 99%
“…An MXene-Ag membrane fouled with methyl green and bovine serum presented at 50 mg/L exhibited remarkable flux recovery (91%-97%) compared to that of the pristine MXene membrane (81%-86%) [191], attributable to the enhanced hydrophilicity of the MXene-Ag membrane with additional nanopores. The water contact angle decreased from 40° to 35° as the Ag nanoparticle level rose from 0 to 21%, confirming that Ag improved membrane surface hydrophilicity [192]. Figure 7(a) shows a schematic of, and the mechanism of dye removal by, the MXene-Ag composite membrane.…”
Section: Membranementioning
confidence: 77%
“…Catecholamine chemistries have been used as a component in a number of different filtration membranes, including gas separation and proton exchange membranes as well as microfiltration (MF), ultrafiltration (UF), nanofiltration (NF), and both forward osmosis and reverse osmosis (RO) membranes . When doing this, care must be taken to avoid both pore blockage and attachment of proteins to the adhesive surface, resulting in reduced filtration performance .…”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%
“…In addition, polydopamine‐based nanocomposite membranes have been exploited to enhance ultrafiltration performance. This includes incorporation of carbon nanotubes, gold nanorods, silica particles, and silver nanoparticles into membranes used to reduce oil, protein, and bacterial fouling in wastewater filtration.…”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%